2021
DOI: 10.1111/sum.12711
|View full text |Cite
|
Sign up to set email alerts
|

Organic fertilizer enhances rice growth in severe saline–alkali soil by increasing soil bacterial diversity

Abstract: The northeast region of China is an important grain‐growing area. However, severe soil salinization in the region impairs plant production. In the present study, organic fertilizer application (composted poultry manure) was evaluated as a potential strategy for remediating saline–alkali soil and promoting rice growth. Following continuous organic fertilizer application for 4 years, the contents of basic cations, including sodium (Na+) and chlorine cations (Cl−), decreased significantly (p < .05) (soil Na + dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 81 publications
2
22
0
Order By: Relevance
“…soil salinity-alkalinity and low soil fertility have been shown to have a negative impact on the growth and yield of crops (Zhang et al, 2021b;Zhou et al, 2021). In the present study, correlation analysis showed that SWC, SSC, and Na + were the key factors affecting wheat yield in saline-alkali soils, whereas soil fertility had no signi cant effect on wheat yield (Fig.…”
Section: Effects Of B and Of Wheat Yieldsupporting
confidence: 44%
“…soil salinity-alkalinity and low soil fertility have been shown to have a negative impact on the growth and yield of crops (Zhang et al, 2021b;Zhou et al, 2021). In the present study, correlation analysis showed that SWC, SSC, and Na + were the key factors affecting wheat yield in saline-alkali soils, whereas soil fertility had no signi cant effect on wheat yield (Fig.…”
Section: Effects Of B and Of Wheat Yieldsupporting
confidence: 44%
“…The TruSeq ® DNA PCR-Free Sample Preparation Kit (Illumina, San Diego, CA, USA) was utilized in library construction, and the Qubit ® 2.0 Fluorometer (Life Technologies, Carlsbad, CA, USA) and qPCR were utilized to quantify the libraries. Then, the libraries were sequenced at the Illumina MiSeq platform described as Zhang et al [32]. All sequence data were submitted to the Sequence Read Archive (SRA: SRP297881) and are freely available at the NCBI (BioProject: PRJNA685114).…”
Section: Library Construction and Sequencingmentioning
confidence: 99%
“…Herewith, as in saline-alkaline soils, salinity soil causes an account of high osmotic stress and ionic stress in plants, which leads to nutrient variability, but also reduces the photosynthesis capacity of the plant. As a result, it causes plant growth and development to stop (Zhang et al, 2022).…”
Section: Research Articlementioning
confidence: 99%